2019
DOI: 10.1002/cssc.201902967
|View full text |Cite
|
Sign up to set email alerts
|

Unique Layer‐Doping‐Induced Regulation of Charge Behavior in Metal‐Free Carbon Nitride Photoanodes for Enhanced Performance

Abstract: Photoinduced charge carrier behavior is critical in determining photoelectrocatalytic activity. In this study, a unique layer‐doped metal‐free polymeric carbon nitride (C3N4) photoanode is fabricated by using one‐pot thermal vapor deposition. With this method, a photoanode consisting of a phosphorus‐doped top layer, boron‐doped middle layer, and pristine C3N4 bottom layer, was formed as a result of the difference in thermal polymerization kinetics associated with the boron‐containing H3BO3–melamine complex and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Thermal vapor deposition was demonstrated as a typical approach to form a multilayered PCN photoanode, namely, a PB−PCN photoanode. 448 In this work, a P-PCN layer, a B-PCN layer, and a pristine M-PCN layer were realized on the top, middle, and bottom positions of the multilayered photoanode, respectively, by thermal condensation of the mixed precursors, namely, a Bcontaining H 3 BO 3 −melamine complex and a P-containing H 3 PO 4 −DCDA complex. The formation of the distinct order of the photocatalytic layer can be attributed to the different thermodynamics and kinetics associated with precursor polymerization, as shown in Figure 30a.…”
Section: Synthesis Of Single-layered Polymeric Carbonmentioning
confidence: 99%
“…Thermal vapor deposition was demonstrated as a typical approach to form a multilayered PCN photoanode, namely, a PB−PCN photoanode. 448 In this work, a P-PCN layer, a B-PCN layer, and a pristine M-PCN layer were realized on the top, middle, and bottom positions of the multilayered photoanode, respectively, by thermal condensation of the mixed precursors, namely, a Bcontaining H 3 BO 3 −melamine complex and a P-containing H 3 PO 4 −DCDA complex. The formation of the distinct order of the photocatalytic layer can be attributed to the different thermodynamics and kinetics associated with precursor polymerization, as shown in Figure 30a.…”
Section: Synthesis Of Single-layered Polymeric Carbonmentioning
confidence: 99%
“…Recently, it was demonstrated that charge transfer and h + extraction properties in CN-PEC are correlated to the order within the CN. [22,23] In the case of a better stacking order of the graphitic layers, a hole extraction efficiency of ~47% was obtained. [24] However, in all the abovementioned scenarios, only one problem was tackled either ediffusion or h + extraction due to synthetic limitations.…”
mentioning
confidence: 99%
“…In the presence of hole scavengers as triethanolamine or redox electrolytes (e.g., polysulfide), , h + extraction efficiencies can be dramatically increased, owing to the fast e – –h + transfer. Recently, it was demonstrated that charge transfer and h + extraction properties in CN-PEC are correlated to the order within the CN. , In the case of a better stacking order of the graphitic layers, a hole extraction efficiency of ∼47% was obtained . However, in all of the above-mentioned scenarios, only one problem was tackled, either e – diffusion or h + extraction due to synthetic limitations.…”
mentioning
confidence: 99%
“…The photocurrent density of K&I co-doped g−CN is approximately 50.3 μA cm −2 at 0.5 V versus Ag/AgCl. Luan et al [ 122 ] reported a unique multi-layer doped non-metal g−CN photoanode using a one-pot TVC. In this structure, a P-doped top layer, B-doped middle layer, and pure g−CN bottom layer were designed to enhance the photocurrent density by nearly nine times that of the pure g−CN.…”
Section: Functionalization Of G−cn Photoelectrodementioning
confidence: 99%
“…Reprinted with permission from ref. [ 122 ] Copyright 2020 Wiley−VCH. ( f ) A diagram illustrating the fabrication of FTO/TiO 2 −nanorod/P−g−CN/metal phosphide electrodes for the PEC water splitting and ( g ) the Tauc plots.…”
Section: Functionalization Of G−cn Photoelectrodementioning
confidence: 99%